If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 3z + -5z + 9 + 4z Reorder the terms: 27 = 9 + 3z + -5z + 4z Combine like terms: 3z + -5z = -2z 27 = 9 + -2z + 4z Combine like terms: -2z + 4z = 2z 27 = 9 + 2z Solving 27 = 9 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 27 + -2z = 9 + 2z + -2z Combine like terms: 2z + -2z = 0 27 + -2z = 9 + 0 27 + -2z = 9 Add '-27' to each side of the equation. 27 + -27 + -2z = 9 + -27 Combine like terms: 27 + -27 = 0 0 + -2z = 9 + -27 -2z = 9 + -27 Combine like terms: 9 + -27 = -18 -2z = -18 Divide each side by '-2'. z = 9 Simplifying z = 9
| -7(3y+2)=8(3y-2) | | 6x+3[2y-x]= | | -2x-39=59-9x | | -9.39+-3.4d=-1.1d+11.08 | | b+3-6b=-3+b | | 2x+3x+-5=90 | | 30-6x=16+8x | | 33-7p=8(1-4p) | | 5x-27=3x+11 | | y=(3x+10)+(-5x+200) | | -2(1-3u)-6=-2(4u+4) | | -6x+3+-9x= | | 6-8x=5x-10x+12 | | 5n+9=2n-3 | | -5=5+y | | -5/3.00=n | | 2.5(-4x-3)=12.5 | | 4y-17=9-9y | | 2-5x+5=3x+10-5x | | 8x+12y=268 | | 6+4p=3+p | | 2(-1)+y=-1+1 | | 3y-1-y= | | 15d-20=35 | | 10(5x-3)=120 | | 2(3x-5)=90 | | 5n-35=5(1-7n) | | 8.75+40x=13.25x+509.00 | | x(1.5x+3)=120 | | 8x+12x=268 | | 7-5m=-8 | | X+13=2x-5 |